2017
DOI: 10.1016/j.comppsych.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Who are likely to attempt suicide again? A comparative study between the first and multiple timers

Abstract: Background Various explanations account for suicide incidents, and some patients continue to attempt afterwards and others never again. The suicide mortality rate increases with the number of serious attempts. The prevention of secondary attempt of suicide should be an important approach to reduce suicide mortality. However, the characteristics of the targeted population of repeated suicide attempters are understudied. Methods This was a cross-sectional data collection from hospital emergency room from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 54 publications
5
23
2
2
Order By: Relevance
“…The female/male ratio was reported to be 0.58 in cases who were presented to the emergency department with a suicide attempt in a survey from China while suicide prevalence was found as 79:100.000 with a female/male ratio of 3 in a study from Thailand. 19,20 In our study, the incidence of suicide was higher in female than in male subjects, but the number and types of drugs ingested were found to be higher in male than in female subjects. This shows that male subjects are using more efficient methods for suicide attempts and have a higher risk of severe complications such as rhabdomyolysis.…”
Section: Discussioncontrasting
confidence: 46%
“…The female/male ratio was reported to be 0.58 in cases who were presented to the emergency department with a suicide attempt in a survey from China while suicide prevalence was found as 79:100.000 with a female/male ratio of 3 in a study from Thailand. 19,20 In our study, the incidence of suicide was higher in female than in male subjects, but the number and types of drugs ingested were found to be higher in male than in female subjects. This shows that male subjects are using more efficient methods for suicide attempts and have a higher risk of severe complications such as rhabdomyolysis.…”
Section: Discussioncontrasting
confidence: 46%
“…In agreement with previous studies [20,21,23,24], this study found an association between loneliness, no close friends, bullying victimization, interpersonal violence and single and/or multiple suicide attempt. Several researchers [13,14] emphasised the importance of mental disorder and/or hopelessness in predicting multiple suicide attempts. These ndings suggest the importance of treating psychosocial distress and prevention of bullying victimization and interpersonal violence in order to prevent suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the number of post-card sent was small, and the efficacy of post-cards is still equivoque in the literature [4,16,1921]. In other studies, multiple attempters were found to show higher intentionality in their attempts, higher levels of psychopathology, and higher risk of reattempt than first-time attempters [22,23].…”
Section: Discussionmentioning
confidence: 99%